Maternal Vitamin C Deficiency during Pregnancy Persistently Impairs Hippocampal Neurogenesis in Offspring of Guinea Pigs - Tveden-Nyborg, Pernille (Public Library of Science, 2012)
While having the highest vitamin C (VitC) concentrations in the body, specific functions of VitC in the brain have only recently been acknowledged. We have shown that postnatal VitC deficiency in guinea pigs causes impairment of hippocampal memory function and leads to 30% less neurons. This study investigates how prenatal VitC deficiency affects postnatal hippocampal development and if any such effect can be reversed by postnatal VitC repletion. Eighty pregnant Dunkin Hartley guinea pig dams were randomized into weight stratified groups receiving High (900 mg) or Low (100 mg) VitC per kg diet. Newborn pups (n = 157) were randomized into a total of four postnatal feeding regimens: High/High (Control); High/Low (Depleted), Low/Low (Deficient); and Low/High (Repleted). Proliferation and migration of newborn cells in the dentate gyrus was assessed by BrdU labeling and hippocampal volumes were determined by stereology. Prenatal VitC deficiency resulted in a significant reduction in postnatal hippocampal volume (P<0.001) which was not reversed by postnatal repletion. There was no difference in postnatal cellular proliferation and survival rates in the hippocampus between dietary groups, however, migration of newborn cells into the granular layer of the hippocampus dentate gyrus was significantly reduced in prenatally deficient animals (P<0.01). We conclude that a prenatal VitC deficiency in guinea pigs leads to persistent impairment of postnatal hippocampal development which is not alleviated by postnatal repletion. Our findings place attention on a yet unrecognized consequence of marginal VitC deficiency during pregnancy.